Bridging Faith and Culture: Unearthing Islamic Values in the Sundanese Munggahan Tradition - Sari, Yunika (Journal of Contemporary Rituals and Traditions, 2023)
This research aims to discuss the Islamic values contained in the Munggahan tradition of the Sundanese tribe as part of welcoming the holy month of Ramadan. The research method used is qualitative with literature review and field study, employing descriptive analysis to analyze complex and clear data. The research includes the understanding of the Munggahan tradition, the Munggahan tradition according to Islamic law, and the Islamic values encompassed in the Munggahan tradition to welcome the holy month of Ramadan in Sundanese culture. The study concludes that the Munggahan tradition is ancestral cultural heritage preserved by the Sundanese people to safeguard Sundanese culture, which is part of Indonesia's cultural wealth. In Islamic law, the Munggahan tradition is permitted and accepted by the Sundanese community, despite the absence of specific Quranic texts governing this tradition. The Munggahan tradition carries numerous wisdom and benefits, embodying Islamic values such as faith, practice, worship, local wisdom, and Islamic brotherhood. This research contributes to our understanding of religious values in the context of Sundanese local culture and emphasizes the importance of preserving Indonesia's cultural heritage based on Islamic teachings.